Wetland mapping from sparse annotations with satellite image time series and temporal-aware segment anything model - Shuai Yuan; Tianwu Lin; Shuang Chen; Yu Xia; Peng Qin; Xiangyu Liu; Xiaoqing Xu; Nan Xu; Hongsheng Zhang; Jie Wang; Peng Gong (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

Coastal land reclamation induced estuarine nutrient-related eutrophication stressors: phenomena, evaluation and management strategies - Linlin Wang; Yuehua Guo; Wenbin Liu; Huaihao Shao; Shuangliang Dai; Lin Mu; Xianzhong Mao; Hongsheng Bi; Kai Zhou; Xiaoyu Lei (Journal of Hydrology, 2026)

Environmental impact analysis of molded pulp cups based on different LCA tools - Nuan Zhang; Qinghua Yang; Qinbao Lin; Yanfei Cheng; Zhihao Zhang; Hongsheng Ma (The International Journal of Life Cycle Assessment, 2026)

Close-packed metal organic frameworks enabled high-energy solid-state lithium metal batteries - Yining Zhang; Hongsheng Shi; Yuyao Zhang; Xin Chen; Shuanghong Wang; Jinjiang Liang; Qiong Yuan; Tianyi Gao; Ran Wei; Haochen Zhang; Tao Li; Tianquan Lin; et al. (Chemical Engineering Journal, 2026)

The balance application of nano-macronutrients promote growth, productivity and quality through modulation of antioxidative activities in wheat - Mingliang Ding; Lijun Tang; Lin Zhang; Yan Yang; Hongsheng Li; Qi Ma; Shaoxiang Li; Jia Liu; Cuiping Zhang; Kun Liu; Shah Fahad; Sidra Fatima; et al. (Plant Science, 2025)

Delayed algal blooms to runoff surges in low-runoff estuaries: hydrodynamic and nutrient driving mechanisms and early warning strategies - Linlin Wang; Zuoyi Chen; Gang Wang; Yike He; Lin Mu; Xianzhong Mao; Hongsheng Bi; Jiabo Zhang (Journal of Hydrology, 2025)

Platinum-copper nanocubezyme facilitate spinal cord recovery via synchronously alleviating oxidative stress and mitigating BNIP3-mediated mitochondrial dysfunction - Xiangge Liu; Cheng Peng; Huiyi Yang; Jiajun Deng; Ping Wu; Yongchun Xiao; Li Wan; Ke Wang; Guowei Zhang; Hua Yang; Jianyu Zou; Judun Zheng; et al. (Chemical Engineering Journal, 2025)

A practice guideline for therapeutic drug monitoring of mycophenolic acid for solid organ transplants - Shuang Liu; Hongsheng Chen; Zaiwei Song; Qi Guo; Xianglin Zhang; Bingyi Shi; Suodi Zhai; Lingli Zhang; Liyan Miao; Liyan Cui; Xiao Chen; Yalin Dong; et al. (Journal of Zhejiang University-SCIENCE B, 2025)
Mycophenolic acid (MPA), the active moiety of both mycophenolate mofetil (MMF) and enteric-coated mycophenolate sodium (EC-MPS), serves as a primary immunosuppressant for maintaining solid organ transplants. Therapeutic drug monitoring (TDM) enhances treatment outcomes through tailored approaches. This study aimed to develop an evidence-based guideline for MPA TDM, facilitating its rational application in clinical settings. The guideline plan was drawn from the Institute of Medicine and World Health Organization (WHO) guidelines. Using the Delphi method, clinical questions and outcome indicators were generated. Systematic reviews, Grading of Recommendations Assessment, Development, and Evaluation (GRADE) evidence quality evaluations, expert opinions, and patient values guided evidence-based suggestions for the guideline. External reviews further refined the recommendations. The guideline for the TDM of MPA (IPGRP-2020CN099) consists of four sections and 16 recommendations encompassing target populations, monitoring strategies, dosage regimens, and influencing factors. High-risk populations, timing of TDM, area under the curve (AUC) versus trough concentration ( C 0 ), target concentration ranges, monitoring frequency, and analytical methods are addressed. Formulation-specific recommendations, initial dosage regimens, populations with unique considerations, pharmacokinetic-informed dosing, body weight factors, pharmacogenetics, and drug–drug interactions are covered. The evidence-based guideline offers a comprehensive recommendation for solid organ transplant recipients undergoing MPA therapy, promoting standardization of MPA TDM, and enhancing treatment efficacy and safety.

Characteristics analysis of the typical vehicle-mounted megawatt-scale heat pipe cooled reactor power system - Henglong Lin; Zeguang Li; Kan Wang; Weilin Zhuge; Ganglin Yu; Hongsheng Jiang; Jingkang Li; Jun Yang; Zilin Su; Huifu Wang (Annals of Nuclear Energy, 2025)

Application and mechanism of Co3O4/Co(OH)2 heterojunctions as matrices for small molecules detection by MALDI-TOF MS - Zufeng Qiu; Kexin Yang; Zijian Huang; Hongsheng Zhao; Zhiwei Lin; Qin Kuang; Zhaoxiong Xie (Journal of Hazardous Materials, 2025)

Precise mitigation strategies for urban heat island effect in Hong Kong's new towns using automated machine learning - Yiyan Li; Hongsheng Zhang; Yinyi Lin; Jing Ling; Huiyuan Xue; Peizhuo Guo (Sustainable Cities and Society, 2025)

Improved machine learning estimation of surface turbulent flux using interpretable model selection and adaptive ensemble algorithms over the Horqin Sandy Land area - Jing Zhao; Yiyi Guo; Hongsheng Zhang; Yihua Lin; Feng Liu; Zhenhai Guo (Atmospheric Research, 2025)

Numerical Simulation of Hydrodynamic Performance of an Offshore Oscillating Water Column Wave Energy Converter Device - Peng Tang; Xinyi Lin; Wei Wang; Hongsheng Zhang (Journal of Marine Science and Engineering, 2024)
Wave energy, as a renewable energy source, plays a significant role in sustainable energy development. This study focuses on a dual-chamber offshore oscillating water column (OWC) wave energy device and performs numerical simulations to analyze the influence of chamber geometry on hydrodynamic characteristics and wave energy conversion efficiency. Unlike existing studies primarily focused on single-chamber configurations, the hydrodynamic characteristics of dual-chamber OWCs are relatively underexplored, especially regarding the impact of critical design parameters on performance. In this study, STAR-CCM+ V2302 software (Version 2410, Siemens Digital Industrial Software, Plano, TX, USA) is utilized to systematically evaluate the effects of key design parameters (including turbine configuration, mid-wall draught depth, and wall angles) on the hydrodynamic performance, wave energy capture efficiency, and wave reflection and loading characteristics of the device. The findings aim to provide a reference framework for the optimal design of dual-chamber OWC systems. The results show that the dual-chamber, dual-turbine (2C2T) configuration offers a 31.32% improvement in efficiency compared to the single-chamber, single-turbine (1C1T) configuration at low wave frequencies. In terms of reducing wave reflection and transmission, the 2C2T configuration outperforms the dual-chamber, single-turbine configuration. When the wall angle increases from 0° to 40°, the total efficiency increases by 166.37%, and the horizontal load decreases by 20.05%. Additionally, optimizing the mid-wall draught depth results in a 9.6% improvement in efficiency and a reduction of vertical load by 11.69%.

Evaluation of power generation capacity of wave energy converter with a controllable-valve buoy based on wave-to-grid modeling and control - Guodong Fan; Weimin Wu; Hongsheng Zhang; Lin Cui; Frede Blaabjerg (Ocean Engineering, 2024)

Multiscale rooftop greening and its socioeconomic implications in Hong Kong - Jing Ling; Ka Hei Anson Yip; Shan Wei; Ka Ying Sit; Liqun Sun; Qingyan Meng; Na Cong; Jian Lin; Hongsheng Zhang (Building and Environment, 2024)

Sea cucumber physiological response to abiotic stress: Emergent contaminants and climate change - Mohamed Mohsen; Sherif Ismail; Xiutang Yuan; Zonghe Yu; Chenggang Lin; Hongsheng Yang (Science of The Total Environment, 2024)

Efficient separation and recovery of barium from barium slag via hydrometallurgical approach: Process design, thermodynamics research and mechanism investigation - Yadong Wu; Junhong Xu; Shuhuan Lin; Hongsheng Huang (Journal of Cleaner Production, 2024)

Methane adsorption effected by pore structure of overmature continental shale: Lower Cretaceous Shahezi Formation, Xujiaweizi Fault, Songliao Basin - Pengfei Zhang; Shuangfang Lu; Nengwu Zhou; Zizhi Lin; Xiangchun Chang; Junjian Zhang; Guo Chen; Yumao Pang; Junjie Wang; Hongsheng Huang; Qi Zhi (Frontiers of Earth Science, 2024)

Carboxymethyl cellulose-based supramolecular hydrogel with thermo-responsive gel-sol transition for temporary plugging of oil pipeline in hot work - Ziteng Yang; Ruixuan Ni; Yang Yang; Jie Qi; Xingyu Lin; Yong Zhang; Li Wang; Yuanpeng Wu; Xiaojiang Li; Hongsheng Lu (Carbohydrate Polymers, 2024)

pH-regulated superhydrophobic quartz sands for controllable oil-water separation - Xingyu Lin; Yong Zhang; Ziteng Yang; Wenjian Yue; Ruoxin Zhang; Jie Qi; Hongsheng Lu (Journal of Environmental Chemical Engineering, 2023)

Microplastics in canned, salt-dried, and instant sea cucumbers sold for human consumption - Mohamed Mohsen; Chenggang Lin; Mohnad Abdalla; Shilin Liu; Hongsheng Yang (Marine Pollution Bulletin, 2023)

A controllable-valve buoy for high-efficiency wave energy conversion under a wide range of wave conditions - Yinan Zhang; Weimin Wu; Hongsheng Zhang; Lin Cui (Ocean Engineering, 2023)

Socioeconomic disparities in cooling and warming efficiencies of urban vegetation and impervious surfaces - Jian Lin; Hongsheng Zhang; Min Chen; Qiang Wang (Sustainable Cities and Society, 2023)

Critical slip line recognition and extraction method of slope based on modified k-medoid clustering algorithm - Yifan Chen; Hongsheng Li; Hang Lin; Yixian Wang; Yanlin Zhao; Yizhou Chen (Computers and Geotechnics, 2023)

Time-frequency analysis framework for understanding non-stationary and multi-scale characteristics of sea-level dynamics - Xindan Liang; Yinyi Lin; Renguang Wu; Gang Li; Nicole Khan; Rui Liu; Hua Su; Shan Wei; Hongsheng Zhang (Frontiers in Marine Science, 2023)
Rising sea level caused by global climate change may increase extreme sea level events, flood low-lying coastal areas, change the ecological and hydrological environment of coastal areas, and bring severe challenges to the survival and development of coastal cities. Hong Kong is a typical economically and socially developed coastal area. However, in such an important coastal city, the mechanisms of local sea-level dynamics and their relationship with climate teleconnections are not well explained. In this paper, Hong Kong tide gauge data spanning 68 years was documented to study the historical sea-level dynamics. Through the analysis framework based on Wavelet Transform and Hilbert Huang Transform, non-stationary and multi-scale features in sea-level dynamics in Hong Kong are revealed. The results show that the relative sea level (RSL) in Hong Kong has experienced roughly 2.5 cycles of high-to-low sea-level transition in the past half-century. The periodic amplitude variation of tides is related to Pacific Decadal Oscillation (PDO) and El Niño-Southern Oscillation (ENSO). RSL rise and fall in eastern Hong Kong often occur in La Niña and El Niño years, respectively. The response of RSL to the PDO and ENSO displays a time lag and spatial heterogeneity in Hong Kong. Hong Kong's eastern coastal waters are more strongly affected by the Pacific climate and current systems than the west. This study dissects the non-stationary and multi-scale characteristics of relative sea-level change and helps to better understand the response of RSL to the global climate system.

Multi-responsive graphene quantum dots hybrid self-healing structural color hydrogel for information encoding and encryption - Jingye Yan; Guoyi Pan; Wenjing Lin; Zilun Tang; Jieheng Zhang; Jiaxin Li; Wenping Li; Xiaofeng Lin; Hongsheng Luo; Guobin Yi (Chemical Engineering Journal, 2023)

Corrigendum: Optimizing cryopreservation of sea cucumber (Apostichopus japonicus) sperm using a programmable freezer and computer-assisted sperm analysis - Shuai Xu; Shilin Liu; Jingchun Sun; Libin Zhang; Chenggang Lin; Lina Sun; Lili Xing; Chunxi Jiang; Hongsheng Yang (Frontiers in Marine Science, 2022)

Spatial patterns and driving factors of carbon stocks in mangrove forests on Hainan Island, China - Yuchen Meng; Ruikun Gou; Jiankun Bai; David Moreno‐Mateos; Charles C. Davis; Luoma Wan; Shanshan Song; Hongsheng Zhang; Xiaoshan Zhu; Guanghui Lin (Global Ecology and Biogeography, 2022)
Aim Mangrove forests are important coastal wetlands for the blue carbon budget and play a significant role in mitigating global climate change. However, spatial patterns of carbon stocks in mangrove forests on an island scale have not been quantified owing to methodological limitations and lack of understanding of controlling factors. We took the entire Hainan Island as a case study and aimed to carry out a comprehensive investigation of the spatial patterns and driving factors of carbon stocks in mangrove forests. Location Southern China. Time period 2017–2020. Major taxa studied Mangrove forest. Methods The upscaling method combined with field surveys and Sentinel‐2 imagery analysis were used to compare different models for optimization of mangrove ecosystem carbon stock estimations. We also used structural equation modelling (SEM) to evaluate the factors driving the distributional patterns of mangrove carbon stocks on an island scale. Results The current total mangrove carbon stock of the entire Hainan Island was estimated to be 703,181 Mg C (with a mean density of 192 Mg C/ha), with the above‐ and below‐ground carbon stocks averaging at 44.7 and 147.3 Mg C/ha, respectively. The mangrove carbon storage in the north‐eastern region of the island was the highest and in the west region the lowest. Sediment nitrogen content and plant species diversity had the most positive driving effects on the distribution of total carbon stock for Hainan Island mangroves. Main conclusions The combination of field surveys and Sentinel‐2 imagery analysis can be applied to regional‐scale estimations of carbon stocks for mangrove forests. Spatial pattens of mangrove carbon stocks vary among locations on Hainan Island, and soil nutrient (especially nitrogen) availability is the dominant factor regulating carbon stock variations along the land‐to‐sea gradient. Our findings have significant implications for better understanding the distribution of mangrove carbon stocks and quantification of the global blue carbon budget.

Optimizing cryopreservation of sea cucumber (Apostichopus japonicus) sperm using a programmable freezer and computer-assisted sperm analysis - Shuai Xu; Shilin Liu; Jingchun Sun; Libin Zhang; Chenggang Lin; Lina Sun; Lili Xing; Chunxi Jiang; Hongsheng Yang (Frontiers in Marine Science, 2022)
The sea cucumber Apostichopus japonicus has high nutritional, medicinal, and economic value. However, factors such as overexploitation, climate change, and environmental pollution have resulted in serious germplasm degradation in both farmed and wild A. japonicus , and it has been listed as endangered on the IUCN (International Union for Conservation of Nature) Red List of Threatened Species. Cryopreservation is an important method to protect germplasm resources and solve the problem of germplasm degradation. Using a programmable freezer and computer-aided sperm analysis, we comprehensively studied and screened the factors that affect the post-thaw motility of A. japonicus sperm during cryopreservation. Based on our results, we propose the following optimal cryopreservation procedure for A. japonicus sperm: cryo-diluent composition of 12.5% dimethyl sulfoxide and 0.1 mol/L glucose, with filter-sterilized (the filter mesh size: 0.45μm) natural seawater (NSW) as the extender; 1:5 mixing ratio of sperm and cryo-diluent; cooling rate and thawing temperatures of 10°C/min and 20°C, respectively. The post-thaw motility of sperm treated using the optimal procedure was > 65%, the fertilization rate (in the blastocyst stage) was nearly 80%, and the hatching rate (in the early auricularia larva stage) was > 65%. Additionally, frozen sperm that had been cryopreserved for 1 year retained a considerable post-thaw motility and fertilization rate compared to recently cryopreserved sperm. We detected obvious differences in sperm freezability among individual A. japonicus , and cryopreservation caused some damage to the sperm structure. In conclusion, our optimized procedure make large-scale cryopreservation of A. japonicus sperm possible, and our results provide valuable information that could be applied to research and conservation of A. japonicus .

Plastic-Associated Microbial Communities in Aquaculture Areas - Mohamed Mohsen; Chenggang Lin; Hamed I. Hamouda; Ahmed M. Al-Zayat; Hongsheng Yang (Frontiers in Marine Science, 2022)
Microorganisms colonize plastics in the aquatic environment but their composition on plastics used in aquaculture remains poorly studied. Microorganisms play a significant role in aquaculture in terms of water quality and the health of cultivated species. In the current study, we explored the composition of microorganisms on floating plastics and their surrounding water collected from ponds and open aquaculture areas. Using scanning electron microscopy, the diversity of microbial communities, primarily diatoms, and bacteria were identified on the plastic surfaces. Additionally, epifluorescence microscopy revealed that prokaryotes were colonized on all plastic samples from 0.1 to 29.27×10 3 cells/cm 2 , with a high abundance found in open aquaculture areas compared to ponds. Bacterial communities were characterized by 16S rRNA sequencing which showed that bacterial communities on plastics were dominated by Proteobacteria, Cyanobacteria, Bacteroidetes, and Actinobacteria. The level of these microbial communities on the plastics differed from those found in the surrounding seawater samples and the abundance of potentially pathogenic bacteria was higher in plastics than in seawater samples. Moreover, hydrocarbon-degrading bacteria were more abundant in the investigated plastic samples than in the water samples. This study contributes to the knowledge regarding the plastisphere community in aquaculture.

Parallel Metabolomic Profiling of Cerebrospinal Fluid, Plasma, and Spinal Cord to Identify Biomarkers for Spinal Cord Injury - Hua Yang; Pengwei Zhang; Min Xie; Jianxian Luo; Jing Zhang; Guowei Zhang; Yang Wang; Hongsheng Lin; Zhisheng Ji (Journal of Molecular Neuroscience, 2022)
Loss of physical and emotional health due to spinal cord injury (SCI) has been rapidly increasing worldwide. Effective evaluation of the severity of SCI is crucial to its prognosis. Herein, we constructed rat models of SCI with four different degrees of injury (sham group, light injury group, moderate injury group, and heavy injury group), using the surgical approach. Cerebrospinal fluid (CSF), plasma, and spinal cord were sampled at the sub-acute spinal cord (72 h post-injury) from each rat. The LC–MS-based metabolic profiling of these samples was performed according to a universal metabolome standard (UMS). The results demonstrated that 130, 104, and 128 metabolites were significantly altered within the CSF, plasma, and spinal cord samples, respectively. Among them, there were four differential metabolites, including uric acid, phosphorycholine, pyridoxine, and guanidoacetic acid, which were commonly identified within the CSF, plasma, and spinal cord samples. Further pathway analysis of these differential metabolites demonstrated a disturbance in the metabolism of glyoxylate and dicarboxylate and glycine, serine, and threonine which were associated with pathophysiologic consequence of spinal cord injury. In particular, phosphorycholine, pyridoxine, and guanidoacetic acid demonstrated a relationship with SCI severity. Thus, they could be utilized as potential metabolite biomarkers for SCI severity assessment.

Alfalfa (Medicago sativa L.) MsCML46 gene encoding calmodulin-like protein confers tolerance to abiotic stress in tobacco - Binghao Du; Naiyu Chen; Lili Song; Dan Wang; Hongsheng Cai; Lin Yao; Xiuting Li; Changhong Guo (Plant Cell Reports, 2021)

Estimating Chinese residential populations from analysis of impervious surfaces derived from satellite images - Shan Wei; Yinyi Lin; Hongsheng Zhang; Luoma Wan; Hui Lin; Zhifeng Wu (International Journal of Remote Sensing, 2021)

Effects of different flow velocities on behavior and TRPA1 expression in the sea cucumber Apostichopus japonicas - Chenggang Lin; Xiaolu Liu; Lina Sun; Shilin Liu; Jingchun Sun; Libin Zhang; Hongsheng Yang (Journal of Oceanology and Limnology, 2020)

Mangrove Species Discrimination from Very High Resolution Imagery Using Gaussian Markov Random Field Model - Luoma Wan; Hongsheng Zhang; Ting Wang; Gang Li; Hui Lin (Wetlands, 2018)

Design, synthesis, and biological evaluation of Cyclobentinib (CB1107) as a potential anti-CML agent - Zijun Zhou; Yang Wang; Jun Li; Baichun Hu; Xiaolin Lin; Ye Chen; Rui Wang; Ju Liu; Hongsheng Liu (Medicinal Chemistry Research, 2018)

Annual dynamics of impervious surfaces at city level of Pearl River Delta metropolitan - Ru Xu; Hongsheng Zhang; Hui Lin (International Journal of Remote Sensing, 2018)

Brain abnormalities in fucosidosis: transplantation or supportive therapy? - Minyan Jiang; Sha Liu; Hua Jiang; Yunting Lin; Yongxian Shao; Hao Hu; Xiaoyuan Zhao; Hongsheng Liu; Yonglan Huang; Li Liu (Metabolic Brain Disease, 2017)

Porcine CD4 promoters and enhancers can direct foreign gene expression in human cells - Xiaochen Lin; Xin Yang; Fuwang Chen; Yuhang Cao; Xiujuan Meng; Jie Jiang; Daxing Pang; Yicheng Zhao; Hongsheng Ouyang; Linzhu Ren (Biotechnology Letters, 2013)

Feature extraction for high-resolution imagery based on human visual perception - Hongsheng Zhang; Hui Lin; Yan Li; Yuanzhi Zhang (International Journal of Remote Sensing, 2013)

Mutation screening of RAD51C in high-risk breast and ovarian cancer families - Wenping Lu; Xianshu Wang; Hongsheng Lin; Noralane M. Lindor; Fergus J. Couch (Familial Cancer, 2012)

Morphology and mechanics of chondroid cells from human adipose-derived Stem cells detected by atomic force microscopy - Simin Luo; Qiping Shi; Zhengang Zha; Ping Yao; Hongsheng Lin; Ning Liu; Hao Wu; Hua Jin; Jiye Cai (Molecular and Cellular Biochemistry, 2012)

Production of cloned transgenic cow expressing omega-3 fatty acids - Xia Wu; Hongsheng Ouyang; Biao Duan; Daxin Pang; Li Zhang; Ting Yuan; Lian Xue; Daibang Ni; Lei Cheng; Shuhua Dong; Zhuying Wei; Lin Li; et al. (Transgenic Research, 2012)

Functional analysis of Waardenburg syndrome-associated PAX3 and SOX10 mutations: report of a dominant-negative SOX10 mutation in Waardenburg syndrome type II - Hua Zhang; Hongsheng Chen; Hunjin Luo; Jing An; Lin Sun; Lingyun Mei; Chufeng He; Lu Jiang; Wen Jiang; Kun Xia; Jia-Da Li; Yong Feng (Human Genetics, 2012)

Toxicity of lead, cadmium and mercury on embryogenesis, survival, growth and metamorphosis of Meretrix meretrix larvae - Qing Wang; Baozhong Liu; Hongsheng Yang; Xiaoyu Wang; Zhihua Lin (Ecotoxicology, 2009)

Characteristics of micrometeorology in the surface layer in the Tibetan Plateau - Liu Huizhi; Zhang Hongsheng; Bian Lin’gen; Chen Jiayi; Zhou Mingyu; Xu Xiangde; Li Shiming; Zhao Yijun (Advances in Atmospheric Sciences, 2002)